THE SOCIAL STATE AS A DIPLOMATIC STRATEGY: LESSONS FROM WORLD HISTORY - Toshpulotov Shokhijakhon Eshpulotovich (PT. Antis International Publisher, 2025)
Objective: This article explores the concept of the social state and its impact on international relations and diplomacy. Grounded in ideals of social justice and citizen welfare, the social state model has shaped global politics. By analyzing historical examples and theoretical insights, the study aims to understand how social welfare policies influence diplomatic strategies, offering lessons that remain relevant in contemporary geopolitics. Method: A qualitative historical-comparative approach was utilized to investigate the social state as a diplomatic tool. The study analyzed academic publications, policy documents, and historical records, focusing on key examples such as post-war Western Europe’s welfare policies, the U.S. New Deal, and social reforms in Nordic countries. Data were organized based on themes like national security, economic diplomacy, and social cohesion, using qualitative analysis to assess the effectiveness of these strategies across various periods. Result: Countries with strong welfare systems, such as Sweden and Germany, effectively projected soft power and built international credibility through their social state models. Economic diplomacy, exemplified by the Marshall Plan, showed how social investments contributed to regional stability and long-term diplomatic relations. Additionally, nations that prioritized social equity and welfare often demonstrated greater internal stability, presenting a united front in international relations. The decline of the Soviet Union serves as a cautionary example of the risks of neglecting social welfare in diplomatic strategies. Novelty: The article highlights the evolving role of the social state in global diplomacy, emphasizing the importance of historical lessons in shaping modern strategies. As the interconnectedness of the world increases, the social state’s role in diplomatic efforts is expected to grow, underscoring the need for countries to adapt their strategies based on past experiences.